Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s00894-011-1308-9
|View full text |Cite
|
Sign up to set email alerts
|

Global and local molecular dynamics of a bacterial carboxylesterase provide insight into its catalytic mechanism

Abstract: Carboxylesterases (CEs) are ubiquitous enzymes responsible for the detoxification of xenobiotics. In humans, substrates for these enzymes are far-ranging, and include the street drug heroin and the anticancer agent irinotecan. Hence, their ability to bind and metabolize substrates is of broad interest to biomedical science. In this study, we focused our attention on dynamic motions of a CE from B. subtilis (pnbCE), with emphasis on the question of what individual domains of the enzyme might contribute to its c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 66 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…183 A C−C bond rotation of Glu310 can facilitate or impede protonation of the active-site His399 residue, causing the enzyme to alternate between active and inactive conformations. Low-frequency motions of two loops are important in substrate conversion by sealing the active site and preventing substrate escape.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…183 A C−C bond rotation of Glu310 can facilitate or impede protonation of the active-site His399 residue, causing the enzyme to alternate between active and inactive conformations. Low-frequency motions of two loops are important in substrate conversion by sealing the active site and preventing substrate escape.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…MD simulation, normal mode calculations, and enzyme kinetics were employed by Yu et al to understand how structural changes in Bacillus subtilis CE affected its catalysis. 183 A C−C bond rotation of Glu310 can facilitate or impede protonation of the active-site His399 residue, causing the enzyme to alternate between active and inactive conformations. Low-frequency motions of two loops are important in substrate conversion by sealing the active site and preventing substrate escape.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…14 All-atom MD simulation of pnb-CE by Wadkins et al has shown that the dynamic motions of coil_5 (residues 61−82) and coil_21 (residues 408−422) located on the surface of pnbCE are critical to the substrate binding. 15 Here, we performed all-atom MD simulations of the wild type and mutant rPPE enzymes, both apo and in complex with (S)-AcO-CPA, to investigate the binding mechanisms of the substrate in different enzymes. Our studies provide insights into why the catalytic activity of the W187H mutant has increased from the perspective of the substrate binding.…”
mentioning
confidence: 99%
“…From the analysis of the crystal structure of a Bacillus subtilis CE (pnb-CE), the “side-door” residues were found to be important for the metabolism of a water-soluble anticancer prodrug CPT-11 (7-ethyl-10-[4-(1-piperidino)-1-piperidino]­carbonyloxycamptothecin) . All-atom MD simulation of pnb-CE by Wadkins et al has shown that the dynamic motions of coil_5 (residues 61–82) and coil_21 (residues 408–422) located on the surface of pnbCE are critical to the substrate binding …”
mentioning
confidence: 99%